Pengembangan Buku Project Based Learning Peradaban Alat Tulis Guna Menumbuhkan Karakter Hormat Siswa - Salsabilla Meita Listiyanti; Gregorius Ari Nugrahanta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to develop a Project-Based Learning (PjBL) book on the civilization of writing tools to foster respect as a character value. Employing an R&D approach with the ADDIE model and a quasi-experimental design, the study engaged ten certified teachers from various regions in the needs analysis stage and ten validators (five certified teachers and five experts) as expert reviewers. The research involved two fourth-grade classes at a public elementary school in Yogyakarta, with class IV A assigned as the control group and class IV B as the experimental group, each consisting of 17 students. Validation results indicated an average score of 3.60 on a 1–4 scale, classified as “very good,” with no revisions required. Experimental testing demonstrated a significant impact of the book on respect (p < 0.05) with a large effect size (r = 0.58; 34.37% contribution). The N-Gain score of 68.81% reflected moderate effectiveness, the z-score calculation results show a clear difference between the lowest achievement in the control group (-2.38) and the highest achievement in the experimental group (1.33), while the Inter-Rater Reliability (IRR) analysis yielded 0.824, categorized as “very high”, thereby reinforcing the validity of findings. In conclusion, the PjBL writing tools civilization book is effective in cultivating respect among elementary school students.